Perancangan Place Identity Ranu Grati Sebagai Upaya untuk Meningkatkan BrandAwareness - Yekti, Rendy Bramestian Pratama; Budiardjo, Hardman; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2017)
Pasuruan is one of the regencies in East Java province has many attractions but not yet terekpose perfectly. Pasuruan not only has a beautiful nature, but also a tourist destination worth to visit. The study was conducted using qualitative research is to conduct interviews, observation, documentation, and literature to obtain data to support the drafting. Data were analyzed using multiple stages of data reduction, data presentation and conclusion. the concept of "Original" presented to provide information to the target audience that Ranu Grati has a natural beauty and beautiful and natural panorama that can be enjoyed by families who want to travel to Ranu Grati. Results from logo creation and media campaign against Ranu Grati is an attempt Travel introduction lake Ranu Grati Pasuruan, East Java, to attract tourists to visit. Besides promoting Ranu Grati which can be enjoyed in various media.  Keywords: Design, Logo, Tourism, Ranu Grati, Pasuruan, East Java, Original.